2008
DOI: 10.1248/cpb.56.1729
|View full text |Cite
|
Sign up to set email alerts
|

Biflavonoids from Daphne feddei and Their Inhibitory Activities against Nitric Oxide Production

Abstract: Bioassay-directed fractionation led to the isolation of two new biflavonoids and 13 known biflavonoids from a sample of the dried stem barks of Daphne feddei. The structures of compounds 1 and 2 were elucidated as 2؆-methoxy-daphnodorin C (1) and 2؆-methoxy-2-epi-daphnodorin C (2) on the basis of detailed spectroscopic analysis and X-ray crystallography. All 15 biflavonoids were tested for inhibitory activities against lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW 264.7 macrophages. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…5 Twenty five isolates were tested for inhibitory activities against LPS-induced NO production in RAW 264.7 macrophages, expert for compounds 8-13 and 5, which had been reported in the our previous paper about Daphne feddei level. 5) Compounds 21 and 24 showed potent inhibitory activities against the production of NO with IC 50 values of 0.006 and 0.076 mM, respectively.…”
Section: Notementioning
confidence: 98%
See 1 more Smart Citation
“…5 Twenty five isolates were tested for inhibitory activities against LPS-induced NO production in RAW 264.7 macrophages, expert for compounds 8-13 and 5, which had been reported in the our previous paper about Daphne feddei level. 5) Compounds 21 and 24 showed potent inhibitory activities against the production of NO with IC 50 values of 0.006 and 0.076 mM, respectively.…”
Section: Notementioning
confidence: 98%
“…1) A literature search revealed no previous phytochemical studies on this plant. In the course of our study on the constituents of thymelaeaceous plants, [2][3][4][5] three new flavonoids, compounds 1-3, together with 29 known flavonoids, were isolated from the titled plant. This paper concerned with the structural elucidation of compounds 1-3 and inhibitory activities of 32 compounds against lipopolysaccharide (LPS)-induced nitric oxide (NO) production in macrophages.…”
Section: Notementioning
confidence: 99%
“…acetone extract prepared from the leaves and stems of D. feddei was partitioned between EtOAc and H 2 O. The EtOAc layer was subjected repeatedly to column chromatography on Si gel, Sephadex LH-20, RP-18, and preparative HPLC to afford compounds 1-11, including two new secolignans and one new neolignan, named feddeiphenols A-C (1-3), together with eight known compounds, kadangustin J (4), 5) surinamensin (5), 6) virolin (6), 6) rosmarinic acid (7), 7) clinopodic acid A (8), 8) vladinol F (9), 9) 9Ј-dehydroxy-vladinol F (10), 10) and isocubebin (11), 4) The structures of the compounds 1-11 were determined as shown in Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been used as a traditional Chinese medicine, named "Dian Rui Xiang" for the treatment of the injuries from falls and bruises. 1) The previous phytochemical studies on Daphne feddei showed that diterpenes, 2) phenylpropanoids, 3) as well as flavonoids 4) are the major components of this plant.…”
mentioning
confidence: 97%
“…[18][19][20][21] Taken together, our results indicate that the diterpenoid compounds from the flower buds of D. genkwa might be valuable candidates for the treatment of various inflammatory disease caused by excessive production of NO.…”
mentioning
confidence: 86%